2017
DOI: 10.1038/bjc.2017.214
|View full text |Cite
|
Sign up to set email alerts
|

Platelet releasate promotes breast cancer growth and angiogenesis via VEGF–integrin cooperative signalling

Abstract: Background:Selective platelet release of pro- or anti-angiogenic factors distinctly regulated angiogenesis. We hypothesised that selective release of platelet angiogenic factors could differently regulate tumour growth.Methods:Breast cancer cell proliferation, cancer cell-induced endothelial tube formation in vitro, and tumour growth in vivo were studied in the presence of protease-activated receptor 1-stimulated platelet releasate (PAR1-PR; rich in pro-angiogenic factors) or PAR4-PR (rich in anti-angiogenic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 29 publications
4
81
0
Order By: Relevance
“…33,34 Platelets are an indicator of tumor activity and angiogenesis, and are associated with tumor growth, invasion, and metastasis by releasing VEGF-integrin cooperative signaling. 35,36 Moreover, lymphocytes are an important component of anticancer immunity and immune surveillance and are associated to prevent the tumor growth and progression. 37,38 Some studies have shown that inflammatory markers and immune-based prognostic indexes were used to evaluate the prognosis of breast cancer, such as NLR, d-NLR, MLR/LMR, and PLR.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Platelets are an indicator of tumor activity and angiogenesis, and are associated with tumor growth, invasion, and metastasis by releasing VEGF-integrin cooperative signaling. 35,36 Moreover, lymphocytes are an important component of anticancer immunity and immune surveillance and are associated to prevent the tumor growth and progression. 37,38 Some studies have shown that inflammatory markers and immune-based prognostic indexes were used to evaluate the prognosis of breast cancer, such as NLR, d-NLR, MLR/LMR, and PLR.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have focused on releasate, which is a refined, centrifuged and purified sample of growth factors released from aggregated platelets when the supernatant is collected, and cellular debris removed . Soluble bioactive molecules in the releasate secreted by the α‐granules of platelets are known to enhance matrix synthesis (eg, TGF‐β), upregulate chemo‐attraction and proliferation in several cell types (eg, PDGF, VEGF, IGF‐I and IGF‐II, EGF and ECGF) (Figure ) and angiogenesis (eg, VEGF, FGF and ECGF) .…”
Section: Overview Of Platelet Biologymentioning
confidence: 99%
“…Based on active metabolism of tumor cells on continuous desire to oxygen and nutrient, they release and produce high amounts of proangiogenic factors that promote nourishing the vessel growth . These are some main positive regulator of angiogenesis, such as vascular endothelial growth factor (VEGF), fibroblast growth factor‐2 (FGF‐2), interleukin‐8 (IL‐8), placental growth factor (PlGF), transforming growth factor beta (TGFbeta), platelet derived growth factor (PDGF), angiopoietins (Angs), etc …”
Section: Introductionmentioning
confidence: 99%